939Longitudinal trends of work productivity in a representative sample of Australians living with multiple sclerosis. (2nd September 2021) - Bessing, Barnabas; Blizzard, Leigh; Hussain, Mohammad A.; Claflin, Suzi B.; Taylor, Bruce V.; Mei, Assoc Ingrid van der
Abstract: Background: studies have documented increased employment rates and MS-related work productivity loss in people living with multiple sclerosis (PwMS). Little is known about the longitudinal trends of work productivity of PwMS. Objectives: To describe the longitudinal patterns of work productivity of PwMS, and examine the factors associated with longitudinal change of work productivity of PwMS. Methods: Study participants were from the Australian MS Longitudinal Study (AMSLS) followed from 2015 to 2018 (n = 2724) who were employed. We described the longitudinal patterns of work productivity and determined the correlates of the changes in work productivity of PwMS. We used linear mixed effect modelling to analyse the data. Results: From our mixed effect model analysis, feelings of depression, walking difficulties, and spasticity problems were independently associated with -1.45 (-1.95 to -0.95), -1.35 (-1.98 to -0.72) and -1.04 (-1.63 to -0.45) per annum change in work productivity respectively. Annual changes in MS symptom clusters: difficulties with walking, balance and spasticity; anxiety and depression; and fatigue and cognitive symptoms were independently associated with -2.53 (-3.53 to -1.52), -1.51 (-2.27 to -0.74), -0.86 (-1.67 to -0.06) percent annual change in work productivity of PwMS respectively. Conclusion: Symptoms cluster like 'difficulties with walking, balance and spasticity', 'feelings of anxiety and depression', and 'fatigue and cognitive symptoms' impact significantly on work productivity. Key messages: MS related annual work productivity loss is marginal but is strongly driven by annual changes in walking difficulties, feelings of depression and spasticity problems